Bagaimana Mahasiswa Menjadi Terlatih Menulis Artikel Ilmiah? - Darmalaksana, Wahyudin (Gunung Djati Conference Series, 2025)
This study aims to examine the factors that contribute to students becoming skilled at writing scientific articles. This study used a qualitative approach using the Participatory Action Research method. The results and discussion indicate that enthusiasm is a key factor in students becoming skilled at writing scientific articles. When theorized, enthusiasm is understood not only from a psychological perspective, but also from a philosophical perspective as a principle, and even as a discipline from a management perspective. The conclusion of this study is that students will certainly be trained in article writing skills to the point of productive publication in scientific journals if enthusiasm is the primary factor. It is not merely a desire without being accompanied by training to improve skills. This study encourages student academics to practice writing scientific articles enthusiastically until they truly become skilled resources.